Förster Resonance Energy Transfer-Based Single-Cell Imaging Reveals Piezo1-Induced Ca2+ Flux Mediates Membrane Ruffling and Cell Survival - Kim, Heon-Su; Suh, Jung-Soo; Jang, Yoon-Kwan; Ahn, Sang-Hyun; Choi, Gyu-Ho; Yang, Jin-Young; Lim, Gah-Hyun; Jung, Youngmi; Jiang, Jie; Sun, Jie; Suk, Myungeun; Wang, Yingxiao; et al. (Frontiers in Cell and Developmental Biology, 2022)
A mechanosensitive ion channel, Piezo1 induces non-selective cation flux in response to various mechanical stresses. However, the biological interpretation and underlying mechanisms of cells resulting from Piezo1 activation remain elusive. This study elucidates Piezo1-mediated Ca2+ influx driven by channel activation and cellular behavior using novel Förster Resonance Energy Transfer (FRET)-based biosensors and single-cell imaging analysis. Results reveal that extracellular Ca2+ influx via Piezo1 requires intact caveolin, cholesterol, and cytoskeletal support. Increased cytoplasmic Ca2+ levels enhance PKA, ERK, Rac1, and ROCK activity, which have the potential to promote cancer cell survival and migration. Furthermore, we demonstrate that Piezo1-mediated Ca2+ influx upregulates membrane ruffling, a characteristic feature of cancer cell metastasis, using spatiotemporal image correlation spectroscopy. Thus, our findings provide new insights into the function of Piezo1, suggesting that Piezo1 plays a significant role in the behavior of cancer cells.